PENGONTROLAN SUHU DAN KELEMBABAN PADA RUANGAN MESIN PEMINTALAN SERAT BENANG - Hidayat, Tatang; Tamaji (Seminar Nasional Ilmu Terapan, 2024)
The textile industry is now entering the Industrial Era 4.0, which aims to increase production efficiency, reduce waste, and reduce costs. In the implementation of Industry 4.0, all production elements, such as equipment, operators, and products, must have intelligence. To achieve this, production machines, especially yarn spinning machines such as blowing and carding, need to be equipped with intelligent devices. Currently, these machines do not meet the requirements due to the lack of a control system that can build intelligence. Therefore, it is important to equip these machines with a monitoring system consisting of data processing modules, sensors, and data processing systems. This monitoring system is very important in the yarn spinning industry, because production control is a crucial aspect in the implementation of Industry 4.0. This study aims to design a monitoring system for blower and carding machines that can provide real-time information on the amount of production, machine operating status, and electricity usage. This data will be displayed in graphical form (dashboard) and can be accessed via a local network using a web browser on a computer or smartphone. With this system, management can monitor production activities in real-time, thereby reducing costs and increasing machine efficiency.